Digital-Era Curriculum Transformation: A Comparative Study of Indonesia and Singapore - Kustiami Kustiami; Bachtiar Sjaiful Bachri; Citra Fitri Kholidya (Journal of Mandalika Social Science, 2026)
Global educational transformation in the Society 5.0 era necessitates adaptive curriculum design. This article presents a comparative analysis of curriculum reform in Indonesia and Singapore by examining its philosophical foundations, recent policy developments in 2026, and implementation strategies. Using a Systematic Literature Review (SLR) method based on 30 credible sources, the study analyzes curriculum transformation through four dimensions: policy foundations, implementation realities, systemic challenges, and technology-driven solutions. The findings indicate that both countries are converging toward the development of twenty-first-century competencies and Artificial Intelligence (AI) literacy. In Indonesia, policy initiatives focus on strengthening the Kurikulum Merdeka through updated regulatory frameworks, whereas Singapore continues to advance its SkillsFuture 2026 agenda and self-directed learning ecosystem. The analysis reveals a persistent gap between policy objectives and classroom-level implementation. Indonesia faces challenges related to infrastructure disparities, bureaucratic demands, and teacher readiness, while Singapore confronts issues associated with student well-being and digital fatigue. This study contributes to the literature by providing a comparative framework for understanding curriculum transformation in different educational contexts. Strategic solutions identified include Smart-Adaptive Learning systems, AI-Augmented Teaching, and performance-based assessment redesign. The findings offer practical insights for policymakers and educational stakeholders seeking to develop more adaptive, equitable, and human-centered curriculum reforms in the digital era.